PENINGKATAN NILAI PERUSAHAAN MELALUI KINERJA KEUANGAN DENGAN GOOD CORPORATE GOVERNANCE SEBAGAI VARIABEL MODERASI - Nurhidayati Nurhidayati; Novianty Novianty; Teguh Setiawan Wibowo; Helmina Br Ginting; Nurul Aini (ITB AAS INDONESIA, 2023)
This study aims to examine and analyze the effect of financial performance on firm value with good corporate governance as a moderating variable. This research is a quantitative research using secondary data. The population of this study are manufacturing companies that are included in the food and beverage industry sub-sector which are listed on the Indonesia Stock Exchange during the 2017-2020 period. The sampling technique used in this study was purposive sampling. The independent variable in this study is company value as measured by return on assets (ROA). The dependent variable in this study is firm value as measured by Tobin's Q. While the moderating variable in this study is good corporate governance as measured by managerial ownership. The collected data was analyzed using multiple linear regression analysis using the SPSS application tool. The results of this study indicate that 1) financial performance has a positive and significant effect on firm value, and 2) good corporate governance is able to moderate the effect of financial performance on firm value. The results of these findings indicate that if the company wants to increase the value of the company, the company must also improve financial performance, besides that to strengthen this increase, the company must also improve good corporate governance.